Mieszkańcy rosyjskiej wsi wobec wyzwań postsowieckiej rzeczywistości w twórczości Iriny Mamajewej - Kalita, Liliana (Studia Rossica Posnaniensia, 2019)
The paper analyses Irina Mamayeva’s short stories and tales that show the life in Russian rural areas during a dozen or so years following perestroika, and point out its influence on both individual life and that of a village community as a group. The picture of the rural areas in the 1990s and at the beginning of the 21st century is pessimistic, filled with images of dilapidating houses, companies being shut down, lack of transport connections. This material destruction is accompanied by the spiritual degradation of the inhabitants: poverty, unemployment, mutual aggression and the feeling of being abandoned by the previous system.